Relationship between patient-reported outcomes and clinical outcomes in metastatic castration-resistant prostate cancer: post hoc analysis of COU-AA-301 and COU-AA-302. (11th December 2017) - Cella, D; Traina, S; Li, T; Johnson, K; Ho, K F; Molina, A; Shore, N D
Abstract: Background: Patient-reported outcomes (PROs) are used to assess benefit-risk in drug development. The relationship between PROs and clinical outcomes is not well understood. We aim to elucidate the relationships between changes in PRO measures and clinical outcomes in metastatic castration-resistant prostate cancer (mCRPC). Patients and methods: We investigated relationships between changes in self-reported fatigue, pain, functional well-being (FWB), physical well-being (PWB) and prostate cancer-specific symptoms with overall survival (OS) and radiographic progression-free survival (rPFS) after 6 and 12 months of treatment in COU-AA-301 ( N = 1195) or COU-AA-302 ( N = 1088). Eligible COU-AA-301 patients had progressed after docetaxel and had Eastern Cooperative Oncology Group performance status (ECOG PS) ≤ 2. Eligible COU-AA-302 patients had no prior chemotherapy and ECOG PS 0 or 1. Patients were treated with abiraterone acetate (1000 mg/day) plus prednisone (10 mg/day) or prednisone alone daily. Association between self-reported fatigue, pain and functional status, and OS and/or rPFS, using pooled data regardless of treatment, was assessed. Cox proportional hazard regression modeled time to death or radiographic progression. Results: In COU-AA-301 patients, PRO improvements were associated with longer OS and longer time to radiographic progression versus worsening or stable PROs ( P < 0.0001). In multivariate models, all except pain intensity remained associated with OS. Pain intensity, PWB and FWB improvements remained associated with rPFS. In COU-AA-302 patients, worsening PROs were associated with higher likelihood of radiographic progression ( P ≤ 0.025) compared with improved or stable PROs. In multivariate models, worsening PWB remained associated with worse rPFS. The 12-month analysis confirmed the 6-month results. Conclusions: PROs are significantly associated with clinically relevant time-to-event efficacy outcomes in clinical trials and may complement and help predict traditional clinical practice methods for monitoring patients for disease progression.